À l'orientale : collecting, displaying and appropriating Islamic art and architecture in the 19th and early 20th centuries - Giese, Francine,; Varela Braga, Ariane, 1978-; Volait, Mercedes, (Arts and Archaeology of the Islamic World;, 2020)
"The present volume offers a collection of essays that examine the mechanisms and strategies of collecting, displaying and appropriating Islamic art in the nineteenth and early twentieth centuries. Many studies in this book concentrate on lesser known collections of Islamic art, situated in Central and Eastern Europe that until now have received little attention from scholars. A section of the volume focuses on the figure of the Swiss collector Henri Moser Charlottenfels, whose important, still largely unstudied collection of Islamic art is now being preserved at the Bernisches Historisches Museum, Switzerland. Contributors to the volume include young researchers and established scholars from Western and Eastern Europe and beyond: Albert Lutz (foreword), Roger Nicholas Balsiger, Moya Carey, Valentina Colonna, Francine Giese, Hélène Guérin, Barbara Karl, Katrin Kaufmann, Sarah Keller, Agnieszka Kluczewska Wójcik, Inessa Kouteinikova, Axel Langer, Maria Medvedeva, Ágnes Sebestyén, Alban von Stockhausen, Ariane Varela Braga, Mercedes Volait. Les contributions de l'ouvrage examinent le mécanisme et les stratégies relatifs à la collection, la présentation et l'appropriation des arts de l'Islam au XIXe siècle et début du XXe siècle. Elles mettent l'accent sur des collections situées en Europe centrale et orientale, lesquelles ont été peu étudiées jusqu'à présent. Une partie de l'ouvrage est dédiée à la figure du collectionneur Suisse Henri Moser Charlottenfels, dont les objets se trouvent aujourd'hui au Bernisches Historisches Museum (Suisse) et qui ont été de même peu étudiés. Les textes émanent de jeunes chercheurs comme de chercheurs confirmés, basés en Europe occidentale et orientale, et au-delà".